Teacher Strategy SMPN 2 Pacet Mojokerto To Improve Student Learning Motivation - Vina Aprilia; Seli Septiana Pratiwi (Buana Pendidikan, 2023)
The purpose of this study was to find out the management of funds, accountability, and the benefits of Dankesis at Prawira Marta Kartasura High School. Dankesis is used for all student activities both for participating in competitions outside of school or for activities made by the students themselves. To support student welfare, it is necessary to have activities that make students happy while at school. The student fund planning is designed by the school principal and deputy of the school. This type of research uses qualitative by taking real data from the school. The data were obtained from interviews and observations at the school.